UJI EFEKTIVITAS REBUSAN BELIMBING WULUH (Averrhoa bilimbi) SEBAGAI PENGAWET ALAMI PADA IKAN TERI JENGKI (Stolephorus heterolobus) ASIN KERING - Lilla Puji Lestari; Evy Ratnasari Ekawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
This study aims to look at the effect of the boiling water treatment by dosage variation star fruit and storage of dried salted anchovy dungarees from microbiological aspects. This research used experimental laboratories methods, using factorial RAL. The results showed that the higher the dosage of boiling water star fruit significantly affect the number of bacteria (p